Predicted and validated theoretical results for stellarators in the frame of eurofusion WPS2 - Castejón, F. (Вопросы атомной науки и техники, 2018)
The main results of the work performed under EUROfusion for stellarator optimization are shown. Physics and engineering activities are undertaken in order that both are considered from the very beginning and the physics optimization takes into account the engineering constrains. are considered The HELIAS (W7-X like) configuration has been chosen as starting point and the physics criteria comprises minimization of NC transport, reduction of bootstrap current in order to have a feasible island-based divertor, reduction of turbulence and improving MHD stability and fast ion confinement. Coils are also simplified and breeding blanket studies together with the power balance of the device. Показано основні результати роботи в рамках ЄВРО-термоядерної програми для оптимізації стеларатора. Фізична та інженерна діяльності наведені для того, щоб оптимізація фізики враховувала інженерні обмеження. Конфігурація ГЕЛІАС (подібна) була обрана в якості відправної точки, а фізичні критерії включають мінімізацію транспорту, зменшення бутстреп-струму, щоб мати можливий острівний дивертор, зниження турбулентності, поліпшення МГД-стабільності і утримання швидких іонів. Котушки спрощені і розмножені з використанням балансу потужності пристрою. Показаны основные результаты работы в рамках ЕВРО-термоядерной программы для оптимизации стелларатора. Физическая и инженерная деятельности приведены для того, чтобы оптимизация физики учитывала инженерные ограничения. Конфигурация ГЕЛИАС (подобная) была выбрана в качестве отправной точки, а физические критерии включают минимизацию транспорта, уменьшение бутстрэп-тока, чтобы иметь возможный островной дивертор, снижение турбулентности, улучшение МГД-стабильности и удержание быстрых ионов. Катушки упрощены и размножены с использованием баланса мощности устройства.